SIMILARITIES AND DIFFERENCES OF MOOD IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - LATIPOVA FAYYOZA (TADQIQOTLAR.UZ, 2024)
ABSTRACT The concept of mood is an important aspect of grammar in both the English and Uzbek languages. Mood refers to the grammatical forms used to indicate the speaker's attitude or the mode of the action, such as declarative, interrogative, imperative, conditional, etc. While English and Uzbek share some similarities in their expression of mood, there are also notable differences between the two languages.This paper provides a comparative analysis of the mood systems in English and Uzbek. It examines the main mood categories in each language, their morphological and syntactic properties, and the semantic nuances they convey. For example, both languages have indicative, imperative, and conditional moods, but Uzbek also has a distinct optative mood that does not directly exist in English grammar.The study also highlights how factors such as word order, case marking, and the use of particles contribute to mood distinctions in Uzbek, which has a more complex and elaborate mood system compared to the more analytical mood system of English. Additionally, the paper discusses how mood interacts with other grammatical categories like tense and aspect in the two languages.By exploring the similarities and divergences in the mood systems of English and Uzbek, this abstract lays the groundwork for a deeper understanding of the typological features and linguistic diversity between these two languages. The findings can inform cross-linguistic studies of modality and have pedagogical implications for teaching these languages as second or foreign languages.